Gender differences in the pathways from childhood disadvantage to metabolic syndrome in adulthood: An examination of health lifestyles - Chioun Lee; Vera K. Tsenkova; Jennifer M. Boylan; Carol D. Ryff (Elsevier, 2018)
We investigate whether socioeconomic status (SES) in childhood shapes adult health lifestyles in domains of physical activity (leisure, work, chores) and diet (servings of healthy [i.e., nutrient-dense] vs. unhealthy [energy-dense] foods). Physical activity and food choices vary by gender and are key factors in the development of metabolic syndrome (MetS). Thus, we examined gender differences in the intervening role of these behaviors in linking early-life SES and MetS in adulthood. We used survey data (n = 1054) from two waves of the Midlife in the U.S. Study (MIDUS 1 and 2) and biomarker data collected at MIDUS 2. Results show that individuals who were disadvantaged in early life are more likely to participate in physical activity related to work or chores, but less likely to participate in leisure-time physical activity, the domain most consistently linked with health benefits. Women from low SES families were exceedingly less likely to complete recommended amounts of physical activity through leisure. Men from low SES consumed more servings of unhealthy foods and fewer servings of healthy foods. The observed associations between childhood SES and health lifestyles in adulthood persist even after controlling for adult SES. For men, lack of leisure-time physical activity and unhealthy food consumption largely explained the association between early-life disadvantage and MetS. For women, leisure-time physical activity partially accounted for the association, with the direct effect of childhood SES remaining significant. Evidence that material deprivation in early life compromises metabolic health in adulthood calls for policy attention to improve economic conditions for disadvantaged families with young children where behavioral pathways (including gender differences therein) may be shaped. The findings also underscore the need to develop gender-specific interventions in adulthood. Keywords: Gender, Childhood SES, Metabolic syndrome, Physical activity, Diet